2022
DOI: 10.1186/s13287-022-02725-2
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells-derived therapies for subarachnoid hemorrhage in preclinical rodent models: a meta-analysis

Abstract: Background Mesenchymal stem cells (MSCs) and MSCs-derived extracellular vesicles (EVs) have emerged as potential novel therapies for subarachnoid hemorrhage (SAH). However, their effects remain incompletely understood. We aim to comprehensively evaluate the effect of MSCs-derived therapies in rodent models of SAH. Methods We searched PubMed, EMBASE, and Web of Science up to September 2021 to identify studies that reported the effects of MSCs or MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Mesenchymal stem cell (MSC) transplantation has emerged as a promising therapeutic approach for subarachnoid hemorrhage (SAH) in rodent models [178]. The therapeutic potential of MSCs in SAH was demonstrated by the intravenous administration of MSCs improving structural integrity and promoting functional recovery in rats subjected to SAH [179][180][181].…”
Section: Exosomal Non-coding Rnas: Diagnostic and Therapeutic Potenti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cell (MSC) transplantation has emerged as a promising therapeutic approach for subarachnoid hemorrhage (SAH) in rodent models [178]. The therapeutic potential of MSCs in SAH was demonstrated by the intravenous administration of MSCs improving structural integrity and promoting functional recovery in rats subjected to SAH [179][180][181].…”
Section: Exosomal Non-coding Rnas: Diagnostic and Therapeutic Potenti...mentioning
confidence: 99%
“…The therapeutic potential of MSCs in SAH was demonstrated by the intravenous administration of MSCs improving structural integrity and promoting functional recovery in rats subjected to SAH [179][180][181]. A study demonstrated that administering bone marrow MSC (BMSC) alle-viated early brain injury (EBI) induced by SAH and reduced neurobehavioral impairments, partly through inhibiting microglia activation [178].…”
Section: Exosomal Non-coding Rnas: Diagnostic and Therapeutic Potenti...mentioning
confidence: 99%
“…MSCs isolated from adult tissues have a broad capacity to proliferate and differentiate into various cell lineages. [39] In recent years, the therapeutic mechanism of MSCs in tissue repair has shifted from one based on cell differentiation and replacement to one based on cell secretion and paracrine signaling. [40] Among the wide range of nutritional factors, MSC-derived exosomes have therapeutic effects in multiple injury or disease indications, including bone defects and OP.…”
Section: The Mechanism Of Action Of Cell-derived Exosomes In the Trea...mentioning
confidence: 99%
“…Non-aneurysmal SAH models are mainly created via two methods: (1) prechiasmatic and cisterna magna blood injection models or (2) endovascular perforation [ 108 ]. These models are widely used, as evidenced by a recent study that used them to test mesenchymal stem cells-derived therapies for SAH as well [ 111 ].…”
Section: Pre-clinical Findingsmentioning
confidence: 99%